Overexpression of the Oncogenic Variant (KLF6-SV1) in Young NPC Patients and Correlation with Lack of E-Cadherin - Saoussen Debouki-Joudi; Sonia Mhirsi; Nihel Ammous-Boukhris; Nehla Mokni-Baizig; Hayet Mhamdi; Said Gritli; Raja Mokdad Gargouri; Mohamed Nejib Marzouki (Analytical Cellular Pathology)
Purpose. The transcription factor Krüppel-like factor 6 (KLF6) regulates various cellular functions, such as metabolism, cell proliferation, and differentiation. KLF6 plays a key role in the development and progression of multiple human cancers. Methods. Fifty primary biopsies and 10 normal nasopharyngeal mucosae were used to analyze by RT-QPCR the expression and the copy number of wtKLF6 and the spliced variants (KLF6-SV1, KLF6-SV2, and KLF6-SV3) in Tunisian patients with nasopharyngeal carcinoma. The expression analysis of E-cadherin and cyclin D1 was conducted by RT-QPCR and Western blot, respectively. Results. The wtKLF6 was significantly downexpressed in tumors compared to normal tissues (p=0.0015), whereas KLF6-SV1 and KLF6-SV2 were overexpressed in tumors compared to wtKLF6 and KLF6-SV3 (p<0.0001). Copy number variation was reduced in tumors compared to normal tissues (p=0.0071). Interestingly, KLF6-SV1 is associated with the juvenile form (p=0.0003) which is more aggressive than the adult form of NPC. Furthermore, the oncogenic variant KLF6-SV1 was overexpressed in tumors lacking the expression of E-cadherin (p=0.0022) suggesting its role in metastasis and tumor progression. The wtKLF6 is associated negatively with cyclin D1 in tumor tissues (p=0.048). Conclusion. The wtKLF6 was downexpressed in contrast with the oncogenic variants. Overexpression of KLF6-SV1 is associated with young patients, and loss of E-cadherin suggests that this variant correlated with the aggressiveness of NPC.